N-Acetyltransferase 2 (NAT2) Acetylator Status among Systemic Lupus Erythematosus Patients from A Tuberculosis Endemic Area in Bandung, Indonesia - Laniyati Hamijoyo; Sasfia Candrianita; Ika Agus Rini; Endang Sutedja; Budi Setiabudiawan; Edhyana Sahiratmadja (The Indonesian Biomedical Journal, 2019)
BACKGROUND: Systemic lupus erythematosus (SLE) patients living in Indonesia are prone to tuberculosis (TB) infection, since this country ranks second globally for TB prevalence. Isoniazid, an anti-tuberculosis (TB) drug, is metabolized by enzyme N-acetyltransferase 2 (NAT2) that is encoded by NAT2 gene. NAT2 haplotype, referring as acetylator status, may predispose as genetic factor in SLE development or complicate SLE therapy. This study explored the NAT2 haplotypes and acetylator status among SLE patients living in a TB endemic area.METHODS: Genomic DNA of 260 registered SLE patients at The Rheumatology Clinic of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia were isolated. NAT2 gene was amplified and sequenced, then NAT2 haplotypes and the acetylator status among SLE patients with or without TB history were determined and presented.RESULTS: Most of SLE patients registered were female (n=250; 96.2%). The median age of patients when SLE was diagnosed for the first time was 27 years old (8-69 years), with organ involvement predominantly in musculoskeletal (80.8%) and mucocutaneous (73.1%). TB history, mostly pulmonary TB, was present in 23.1% of SLE patients of whom TB was diagnosed before SLE (10.4%) or after SLE (10.7%) or both before and after SLE (2%). The acetylator status was mostly intermediate (61.5%) with the NAT2*4/*6B was the most prevalent haplotype (25.8%).CONCLUSION: There is a high number of intermediate and low acetylator status among SLE patients. Since these SLE patients live in TB endemic area, the NAT2 acetylator status determination among SLE patients before starting TB therapy may have clinical benefit to decrease a possible drug induced liver injury, and this warrants further study.KEYWORDS: NAT2, acetylator, systemic lupus erythematosus, tuberculosis